Muslim Perspectives on Islamophobia: From Misconceptions to Reason: Oleh Zouhir Gabsi - Feiziya (Fay) Patel (Asosiasi Teolog Indonesia, 2026)
A book review of Muslim Perspectives on Islamophobia: From Misconceptions to Reason